Evaluation of organic substitution based on vegetable yield and soil fertility. Issue 1 (31st December 2022) - Hu, Guo-Qing; Ma, Xi-Xian; Li, Xu-Hua; Wang, Hui
ABSTRACT: Recultivation of abandoned farmland (AF) is a supplement to land resources. However, less is known about the effects of different organic substitution rates (OSRs) on soil fertility under AF recultivation. We investigated the response of vegetable yields and soil physicochemical and microbial properties to five OSRs (0, 25%, 50%, 75%, and 100%) in an AF. Single chemical fertilizer treatment (0 OSR) had the highest yield (54.4 and 24.8 t hm −2 ) and nitrate content (1118.8 and 341.5 mg kg −1 ) of Chinese cabbage and spinach. With the increase of OSRs, vitamin C content gradually increased in both vegetables. Organic substitution had a positive effect on the main soil fertility indicators. Although 50% and 75% OSRs had not the highest vegetable yield, but they significantly improved vegetable quality and soil fertility. Therefore, it is feasible to increase or maintain soil fertility by organic substitution under AF recultivation.